2018
DOI: 10.1049/iet-net.2017.0240
|View full text |Cite
|
Sign up to set email alerts
|

Optimised approach based on hybrid MAC protocol for M2M networks

Abstract: In machine-to-machine (M2M) networks, the ability to access the radio channel requires a rigid design of a medium access control (MAC) protocol. Here, an optimised hybrid MAC protocol will be proposed which is composed of two main processes, the contending process and the transmission process. During contention process, the devices randomly contend the transmission opportunities with equal probabilities by using the conventional-based slotted ALOHA (S-ALOHA) mechanism. Only successful devices can assign a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…The devices that successfully contend in the contention period are assigned a time slot for data transmission in the transmission period. A similar hybrid MAC protocol is proposed in [33], wherein slotted ALOHA is used in the contention period and reservationbased time division multiple access (TDMA) is used in the transmission period. The protocol proposed in [32] is extended to heterogeneous M2M networks in [34], wherein different types of devices with different service requirements and priorities are considered.…”
Section: Related Workmentioning
confidence: 99%
“…The devices that successfully contend in the contention period are assigned a time slot for data transmission in the transmission period. A similar hybrid MAC protocol is proposed in [33], wherein slotted ALOHA is used in the contention period and reservationbased time division multiple access (TDMA) is used in the transmission period. The protocol proposed in [32] is extended to heterogeneous M2M networks in [34], wherein different types of devices with different service requirements and priorities are considered.…”
Section: Related Workmentioning
confidence: 99%
“…Gbr. 1 memperlihatkan desain komunikasi M2M yang terdiri atas domain perangkat, domain jaringan, dan domain aplikasi [3]. Pengiriman data dimulai ketika PKM menginformasikan permintaan ke PKMG, kemudian PKMG mengindera saluran dan mengirimkan hasilnya ke PKM.…”
Section: Pendahuluanunclassified
“…A case study of industrial application has been taken by Meinyk et al [14], where the study found different hybrid MAC applicable over the resource-constrained wireless transmission. Saad et al [15] have offered an optimized scheme focusing on machine-to-machine communication using a hybrid MAC system where Monte-Carlo simulation has been used. Apart from this, there are various other approaches, e.g., Yang et al [16], Deng et al [17], Ma et al [18], Jeon et al [19],Cao et al [20], Alam and Kim [21], Nguyen et al [22], Yang et al [23], Liu et al [24], Hu et al [25].…”
Section: Related Workmentioning
confidence: 99%